Homeopathic treatment in addition to standard care in multi drug resistant pulmonary tuberculosis: a randomized, double blind, placebo controlled clinical trial - Chand, Kusum S; Manchanda, Raj K; Mittal, Renu; Batra, Sudhir; Banavaliker, Jayant N; De, Indra (Homeopathy, 2014)
Background: Multi drug resistant-tuberculosis (MDR-TB) [resistant to Isoniazid and Rifampicin] is a major global public health problem. In India the incidence is rising in spite of implementation of Revised National Tuberculosis Control Program. Standard MDR-TB drugs are second generation antibiotics taken for 24–27 months. The present study was undertaken to evaluate the efficacy of add on homeopathic intervention to the standard MDR-TB regimen (SR).Methods: A randomized, double blind, placebo controlled study was conducted from 2003 to 2008. 120 diagnosed MDR-TB patients (both culture positive and negative) were enrolled and randomized to receive Standard Regimen + individualized homeopathic medicine (SR + H) or Standard Regimen + identical placebo (SR + P). The medicines have been used in infrequent doses. The outcome measures were sputum conversion, changes in chest X-ray (CXR), hemoglobin, erythrocyte sedimentation rate (ESR), weight gain, and clinical improvement.Results: There was an improvement in all the outcome measures as per intention to treat (ITT) and per protocol (PP) analyses. ITT analyses revealed sputum culture conversion from positive to negative in 23 (38.3%) in SR + H; 23 (38.3%) patients in SR + P group; (p = 0.269) and 27 (55.1); 21 (42.8%), p = 0.225 as PP analyses. The mean weight gain in SR + H group was 2.4 ± 4.9 and in SR + P was 0.8 ± 4.4; [p = 0.071], reduction in ESR in SR + H was −8.7 ± 13.2; SR + P was 3.9 ± 15.4 [p = 0.068]. The mean increase in hemoglobin was by 0.6 ± 1.7 in SR + H & 0.3 ± 2.3 [p = 0.440] in SR + P group at 95% confidence interval. Statistically significant improvement was seen in CXR in 37 (61.7%) in SR + H and 20 (33.3%) patients in SR + P group (p = 0.002).Subgroup analyses of culture positive patients showed statistically significant improvement in CXR (p = 0.0005), weight gain (p = 0.026), increase in hemoglobin (p = 0.017) and reduction in ESR (p = 0.025) with add on homeopathy. The cure rate was 11.4% more in SR + H group as compared to placebo group. Change in sputum culture conversion, was not statistically significant.Conclusion: Add on homeopathy in addition to standard therapy appears to improve outcome in MDR-TB. Larger scale studies using a standardized homeopathic treatment regime should be conducted.
Keywords: Multi drug resistant-tuberculosis (MDR-TB); Standard MDR-TB regimen randomized; Double blind; Placebo controlled trial; Sputum conversion; Radiological changes; Add on homeopathy; Efficacy